Influence of dissolved organic matter and manganese oxides on metal speciation in soil solution: A modelling approach. (June 2016) - Schneider, Arnaud R.; Ponthieu, Marie; Cancès, Benjamin; Conreux, Alexandra; Morvan, Xavier; Gommeaux, Maxime; Marin, Béatrice; Benedetti, Marc F.
Abstract: Trace element (TE) speciation modelling in soil solution is controlled by the assumptions made about the soil solution composition. To evaluate this influence, different assumptions using Visual MINTEQ were tested and compared to measurements of free TE concentrations. The soil column Donnan membrane technique (SC-DMT) was used to estimate the free TE (Cd, Cu, Ni, Pb and Zn) concentrations in six acidic soil solutions. A batch technique using DAX-8 resin was used to fractionate the dissolved organic matter (DOM) into four fractions: humic acids (HA), fulvic acids (FA), hydrophilic acids (Hy) and hydrophobic neutral organic matter (HON). To model TE speciation, particular attention was focused on the hydrous manganese oxides (HMO) and the Hy fraction, ligands not considered in most of the TE speciation modelling studies in soil solution. In this work, the model predictions of free ion activities agree with the experimental results. The knowledge of the FA fraction seems to be very useful, especially in the case of high DOM content, for more accurately representing experimental data. Finally, the role of the manganese oxides and of the Hy fraction on TE speciation was identified and, depending on the physicochemical conditions of the soil solution, should be considered in future studies. Highlights: The speciation of Cd, Cu, Ni, Pb and Zn is studied in acidic soil solutions. Cd, Ni and Zn occur as free ions while Cu and Pb are also complexed to ligands. LMWOA have more impact on Ni and Zn speciation than FA. FA proportions usually used in modelling studies are overestimated. HMO has an impact on Pb speciation and should not be neglected in modelling studies. Abstract : The impact of HMO and Hy fraction of DOM (two ligands often neglected in the modelling studies) on the speciation of TE in soil solution has been highlighted.